Proposed Legislative solutions to Adopt the Community Service Sentence in the Iraqi Criminal legislation Comparative Study - MOHAMMED, LATEEFAH (Journal of Legal Sciences, 2022)
The community service in its various forms topped up the alternative short term custodial sentence in some crimes, and experience has shown the success of this alternative in sparing the convicted negative effects of custodial sentences in all social, psychological and even economic aspects and on the other hand addressing the problem of overcrowding prisons. This penalty consists of requiring the convicted person to work certain hours in specific areas and within a certain period determined by the legislator. Through comparative analytical studies between Western and Arab legislation, we found there are such major differences in the ways in which [community service] has been worked out that it is impossible, indeed irresponsible, to transpose the experiences of one country upon another, providing for it as an original punishment sometimes or an alternative custodial sentences for imprisonment for certain crimes or alternative to physical coercion, under which legislation has set the maximum penalty for the deprivation of liberty that the court may replace in exchange for the imposition of community service for specific hours determined by the provision unpaid in certain quarters determined by the legislator or the decision issued under it, taking into account certain controls in The most important of these is the consent of the convict and not to harm his dignity. In line with the modern punitive policy, we have proposed to the Iraqi legislator to amend some of the provisions of the Penal Code to allow the adoption of this punishment in its various forms, either as an original punishment for crimes of violations and misdemeanours or by replacing community service instead of  some of the punishments that are causes negative consequences  for the freedom prescribed for some crimes of misdemeanours and violations or alternative to physical coercion, in accordance with certain controls derived from comparative legislation, with the introduction of judicial oversight that will apply it in accordance with its purposes, which seek to qualify sentenced away from the walls of the penal facility.